THE EFFECT OF WAIST FLEXIBLE, BODY MASS INDEX, AND CONFIDENCE ON THE ACCURACY OF SMASH BALL VOLLEY - Kemal Hidayatullah; Kamal Firdaus (LP3M Universitas Muhammadiyah Muara Bungo, 2022)
This study aims to analyze the effect of waist flexibility, Body Mass Index (BMI), and confidence on the accuracy of volleyball smashes. This type of research is quantitative associative with a path analysis approach. A total of 25 male volleyball athletes at UKM STKIP Muhammadiyah Muaro Bungo were used as research samples, who were recruited using purposive sampling. The waist flexibility instrument uses a flexiometer, BMI uses anthropometry, self-confidence uses a questionnaire, and the volleyball smash accuracy test. Data were analyzed using path analysis through structural model testing. The results showed: (1) there was a direct effect of waist flexibility on the accuracy of volleyball smashes (py1 = 0.285 or 8.12%), (2) there was a direct effect of BMI on the accuracy of volleyball smashes (py2 = 0.216 or 4.67%), (3) there was a direct effect of self-confidence on the accuracy of volleyball smashes (py3 = ​​0.622 or 38.69%), (4) there is an indirect effect of waist flexibility on the accuracy of smash through self-confidence (p31.py3 = ​​0.312 > py1 = 0.285 or the total effect 35.60%), (5) there is an indirect effect of BMI on the accuracy of smash through self-confidence (p32.py3 = ​​0.242 > py2 = 0.216 or the total effect 20.97%), and (6) there is an effect of waist flexibility, BMI, and self-confident simultaneously on the accuracy of volleyball smashes (Rsquare = 0.891 or 89.10%).